Analysis of Legal Reasoning of Judge's Decision Number 1429/Pdt.G/2013/Pa.Tng about Hadhanah Child Custody Rights to Non-Muslim Husbands under Positive Law and Compilation of Islamic Law - Elsa Putri Supriyanto; M. Junaidi (Universitas Muhammadiyah Surakarta, 2024)
The purpose of this research is to analyze the basis of legal reasoning for the judge's decision Number 1429/Pdt.G/2013/Pa.Tng regarding child custody of non-Muslim husbands discussed in positive law and the legal context of the Compilation of Islamic Law. The research method used is a literature analysis of the judge's decision and related laws and regulations with a normative approach that refers to relevant legal theories and legal doctrines. The results of the analysis show that the legal reasoning in the decision is strongly influenced by the provisions of the applicable positive law and also reflects the consideration of Islamic law in the codification of Islamic law. The findings provide a deeper understanding of how courts apply positive and Islamic law in resolving cases involving various aspects of family law, particularly cases concerning child custody in interfaith marriages. The implications of this analysis contribute to the development of more comprehensive legal thinking and judicial practice, particularly in the context of Indonesia's legal pluralism.